Amoxicillin Loaded Hollow Microparticles in the Treatment of Osteomyelitis Disease Using Single-Nozzle Electrospinning - GÜNDÜZ, OĞUZHAN (SPRINGER, 2018)
In this study, hollow microparticles were produced with polymethylsilsesquioxane/chitosan/bovine hydroxyapatite/hexagonal boron nitride (PCBB) polyblend using single-nozzle electrospinning method. Also, hollow microparticles are loaded with amoxicillin (AMX) and their drug delivery capabilities have been studied according to a treatment of osteomyelitis disease. The morphology, chemical groups, particle size, antimicrobial activity, and AMX drug release were systematically studied using scanning electron microscopy (SEM), optical microscopy, Fourier transformation infrared spectroscopy (FTIR), hollow microparticle size measurements, antimicrobial activity test, and UV spectroscopy. In vitro biocompatibility was analyzed with human bone osteosarcoma (U2OS) cell line. This present work can help in the design of a drug delivery platform for antimicrobial effect and bone repair at the same time for osteomyelitis disease treatment.
Keywords: Single-nozzle electrospinning; Hollow microparticles; Osteomyelitis; Drug delivery; Bone tissue engineering; SILICA NANOPARTICLES; MESOPOROUS SILICA; BONE; INFECTION; MICROSPHERES; PENETRATION; FABRICATION; NANOFIBERS; STABILITY; PARTICLES